2007
DOI: 10.1007/s10195-007-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Cement mantle defects in total hip arthroplasty: influence of stem size and cementing technique

Abstract: The cause of isolated osteolysis in the femoral shaft around stem implants in patients with cemented THR has so far not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It can be difficult to achieve this in capacious Dorr-type C stovepipe femurs. There is little understanding regarding the distal cement mantle length and loosening [29,30]. Vancouver C-type injuries were associated in the current study with stovepipe femurs and low cortical thickness, and in these patients, cement mantle length did appear to play a role.…”
Section: Discussionmentioning
confidence: 49%
“…It can be difficult to achieve this in capacious Dorr-type C stovepipe femurs. There is little understanding regarding the distal cement mantle length and loosening [29,30]. Vancouver C-type injuries were associated in the current study with stovepipe femurs and low cortical thickness, and in these patients, cement mantle length did appear to play a role.…”
Section: Discussionmentioning
confidence: 49%
“…But the size of the pore and their distribution are expected to strongly affect the fracture strength if some of the pores exceed the critical flaw size for PMMA (John et al 2007). Pores at the interface between the cement and femoral stem can also act as sites of stress concentration, with the potential for crack emanating from micropores initiation; the number of these pores can be decreased by preheating the femoral stem , Spears et al 2001, Katzer et al 2008, but the interaction between these defects has not been studied too, which is the aim of our work. These defects can also act as sites of stress concentration which the level reaches or exceeds, locally, the tensile strength of the cement (Murphy and Prendergast 2001): see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Most cracks in cement mantle were originated from pores in bone cement, which results in loosening of prosthesis. Cementing technique, like vacuum mixing, reduces 70–80% pore area compared with non-vacuum mixing 3 . It was observed that with increase in the penetration depth the stresses at bone/bone cement also increased.…”
Section: Introductionmentioning
confidence: 99%